Relatedness defies biogeography: the tale of two island endemics (Acacia heterophylla and A. koa). Issue 1 (18th June 2014) - Le Roux, Johannes J.; Strasberg, Dominique; Rouget, Mathieu; Morden, Clifford W.; Koordom, Megan; Richardson, David M.
Summary: Despite the normally strong link between geographic proximity and relatedness of recently diverged taxa, truly puzzling biogeographic anomalies to this expectation exist in nature. Using a dated phylogeny, population genetic structure and estimates of ecological niche overlap, we tested the hypothesis that two geographically very disjunct, but morphologically very similar, island endemics ( Acacia heterophylla from Réunion Island and A. koa from the Hawaiian archipelago) are the result of dispersal between these two island groups, rather than independent colonization events from Australia followed by convergent evolution. Our genetic results indicated that A. heterophylla renders A. koa paraphyletic and that the former colonized the Mascarene archipelago directly from the Hawaiian Islands ≤ 1.4 million yr ago. This colonization sequence was corroborated by similar ecological niches between the two island taxa, but not between A. melanoxylon from Australia (a sister, and presumed ancestral, taxon to A. koa and A. heterophylla ) and Hawaiian A. koa . It is widely accepted that the long‐distance dispersal of plants occurs more frequently than previously thought. Here, however, we document one of the most exceptional examples of such dispersal. Despite c . 18 000 km separating A. heterophylla and A. koa, these two island endemics from two different oceans probably represent a single taxon as a result of recent extreme long‐distance dispersal.